Histological, histochemical and ultrastructural study of slipped capital femoral epiphysis. (1st April 2017) - Tresoldi, I.; Modesti, A.; Dragoni, M.; Potenza, V.; Ippolito, E.
Abstract: Purpose: The purpose of our study was to investigate the histological, histochemical and ultrastructural aspects of the proximal femoral growth plate in slipped capital femoral epiphysis (SCFE). Methods: Eight core biopsies of the proximal femoral growth plate were performed during in situ epiphysiodesis in patients with SCFE that was at the pre-slipping stage in two cases and at the mild slipping stage (Southwick angle < 30°) in six cases. After fixation, the specimens were processed for either histological or histochemical or ultrastructural studies. Results: The proximal femoral growth plate was thicker than normal in the SCFE cases, and the 3:1 ratio between the thickness of the resting zone and the other zones of the plate was reversed. Chondrocytes of the proliferating, maturation, hypertrophic and degenerating zones were arranged in large clusters rather than in columns, which were separated by loose fibrillary septae that appeared moderately alcian blue positive and metachromatic. The collagen fibrils of the longitudinal septae were uniformly thin, measuring about 200 Å, whereas in the normal plate collagen fibrils were in the range of 300 to 1200 Å in thickness. Chondrocytes were elongated and smaller than normal, with a dark cytoplasm. In the degenerating zone, mineralisation of the longitudinal and transversal septae was scanty and enchondral ossification was impaired, with a few small osteoblasts forming thin bone trabeculae on the cartilage septae of the degenerating zone. Conclusion: In SCFE, the proximal femoral growth plate undergoes several histological, histochemical and ultrastructural changes that precede slipping of the epiphysis since they are already present at a pre-slipping stage of the disease. The loss of solidity of the extracellular matrix and the disarrangement of the normal architecture of the physis very likely cause the consequent slipping of the proximal femoral epiphysis. SCFE aetiology remains unknown.